2020
DOI: 10.1111/cp.12194
|View full text |Cite
|
Sign up to set email alerts
|

The buffer role of psychological flexibility against the impact of major life events on depression symptoms

Abstract: Purpose Major life events have been positively associated with depression symptoms. Although psychological flexibility has been associated with adaptive coping skills and negatively linked with depression symptoms, it remains unclear whether psychological flexibility may be a protective process against the pervasive impact of major life events. Thus, the present study aimed to explore the moderating effect of psychological flexibility on the association between the cumulative number of major life events and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 40 publications
5
28
0
2
Order By: Relevance
“…The role of psychological flexibility as a protective psychological resource during a pandemic and associated social restrictions is consistent with prior research showing that psychological flexibility is related to better mental health in a wide range of contexts ( Gloster et al, 2017 ; Hayes et al, 2006 ; Kashdan & Rottenberg, 2010 ; Stabbe et al, 2019 ). Results of this study that show psychological flexibility moderates the relationship between risk factors associated with the COVID-19 lockdown and mental health are consistent with prior research, which demonstrates similar moderation effects of daily stress ( Gloster et al, 2017 ), learned helplessness Trindade, Mendes, & Ferreira, 2020 ) and major life events ( Fonseca et al, 2019 ) on mental health in the general population.…”
Section: Discussionsupporting
confidence: 88%
“…The role of psychological flexibility as a protective psychological resource during a pandemic and associated social restrictions is consistent with prior research showing that psychological flexibility is related to better mental health in a wide range of contexts ( Gloster et al, 2017 ; Hayes et al, 2006 ; Kashdan & Rottenberg, 2010 ; Stabbe et al, 2019 ). Results of this study that show psychological flexibility moderates the relationship between risk factors associated with the COVID-19 lockdown and mental health are consistent with prior research, which demonstrates similar moderation effects of daily stress ( Gloster et al, 2017 ), learned helplessness Trindade, Mendes, & Ferreira, 2020 ) and major life events ( Fonseca et al, 2019 ) on mental health in the general population.…”
Section: Discussionsupporting
confidence: 88%
“…Although these results do not demonstrate a cause-effect relationship between changes in psychological inflexibility and changes in mental health symptoms because the associations are crossectional (see Cole & Maxwell, 2003 ), our results are nonetheless congruent with the theory that psychological inflexibility likely interferes with effective coping under distress and leads to poor mental health (e.g., Dawson & Golijani-Moghaddam, 2020 ; Karekla & Panayiotou, 2011 ). The results are also akin to the finding that lack of psychological flexibility may diminish resilience to accumulated major life events and their perceived negative impact ( Fonseca et al, 2019 ).…”
Section: Discussionmentioning
confidence: 56%
“…Conversely, psychological inflexibility involves a rigid behavioral pattern characterized by persistent avoidance of aversive internal and external events (experiential avoidance: Hayes et al, 1996 ; Luciano & Hayes, 2001 ) that interferes with engagement in personally valued actions. Research shows that psychological flexibility consistently moderates (mitigates) the detrimental impact of stress on wellbeing and mental health ( Gloster et al, 2017 ), buffering the effect of accumulated major life events and their perceived negative impact ( Fonseca et al, 2019 ). More broadly, there is substantial evidence that high psychological flexibility predicts wellbeing while high psychological inflexibility is consistently associated with distress, psychopathology, and poor mental health ( Bluett et al, 2014 ; Bond et al, 2011 ; Gloster et al, 2011 ; Kashdan & Rottenberg, 2010 ; Levin et al, 2014 ; Marshal & Brockman, 2016 ; Tyndall et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, improving psychological flexibility and reducing anxiety favor better mental health outcomes, even in more stressful situations like a pandemic. Some studies have confirmed that enhancing personal resources guarantees a better response to unfavorable and unpredictable circumstances [ 49 ], including during the pandemic [ 50 , 51 ]. Nevertheless, the second hypothesis was not completely confirmed as mindfulness was not a predictor of general psychosocial functioning.…”
Section: Discussionmentioning
confidence: 99%